Economic growth and energy consumption causal nexus viewed through a bootstrap rolling window - Balcilar, Mehmet; Ozdemir, Zeynel Abidin; Arslanturk, Yalcin (Elsevier Science Bv, 2010)
One puzzling results in the literature on energy consumption-economic growth causality is the variability of results particularly across sample periods, sample sizes, and model specification. In order overcome these issues this paper analyzes the causal links between energy consumption and economic growth for G-7 countries using bootstrap Granger non-causality tests with fixed size rolling subsamples. The data used includes annual total energy consumption and real Gross Domestic Product (GDP) series from 1960 to 2006 for G-7 countries, excluding Germany, for which the sample period starts from 1971. Using the full sample bootstrap Granger causality test, we find that there is predictive power from energy consumption to economic growth only for Canada. However, parameter instability tests show that none of the estimated models have constant parameters and hence the full sample results are not reliable. Analogous to the full sample results, the results obtained from the bootstrap rolling window estimation indicate no consistent causal links between energy consumption and economic growth. We, however, find that causal links are present between the series in various subsamples. Furthermore, these subsample periods correspond to significant economic events, indicating that the findings are not statistical artefacts, but correspond to real economic changes. Our results encompass previous findings and offer an explanation to varying findings. (C) 2010 Published by Elsevier B.V.
Keywords: Economic growth; Energy consumption; Bootstrap; Time-varying causality